Completeness of reporting in abstracts of randomized controlled trials in dental medicine published from 2015–2023: A methodological study - Nensi Bralić; Livia Puljak; Barbara Ćaćić; Israel Junior Borges do Nascimento; Marija Šimundić Munitić; Marina Krnić Martinić; Tonia Škoprc; Andrija Babić; Jelena Zekan; Ivana Vukičević; Tina Poklepović Peričić (PLoS ONE, 2025)
Background Well-reported scientific abstracts are essential as they provide a concise summary of key research findings. Our study aimed to assess the completeness of reporting in abstracts of randomized controlled trials (RCTs) in dental medicine using the CONSORT for Abstracts (CONSORT-A) checklist. Methods This was a methodological cross-sectional study. We searched PubMed for RCTs published between August 2015 and August 2023 in Q1 journals from the “Dentistry, Oral Surgery & Medicine” category of the Journal Citation Reports. Two authors independently screened the records and assessed their adherence to 15 CONSORT-A items (items Authors and Recruitment were not assessed) for each abstract. All items were scored with ‘1’ if reported adequately (in line with CONSORT-A), ‘0’ if reported inadequately, and ‘0.5’ if the reporting was partially adequate. We calculated each abstract’s adherence (percentage) rate and median adherence across all abstracts. The adherence to CONSORT-A items was determined by dividing the number of articles that reported each item adequately by the total number of articles included. We also conducted a Jonckheere-Terpstra trend test to assess the temporal trend. Results The search resulted in 1691 records, of which 1564 were eligible for inclusion. We analyzed a random sample of 400 abstracts. Median adherence to CONSORT-A overall was 43.3% (95% CI 43.3 to 43.3). Items with the highest adherence scores were ‘Conclusions’, ‘Objective’, and ‘Interventions’, while ‘Funding’, ‘Randomization’, and ‘Harms’ had the lowest adherence scores. Median adherence to CONSORT-A has not improved over time (p = 0.342). For each analyzed year, mean adherence to CONSORT-A was around 40%. Conclusions Reporting in abstracts of RCTs in dental medicine was suboptimal, and there was no improvement from 2015 to 2023. Improved guideline enforcement and author education are vital for enhancing abstract reporting quality and transparency.